Identifying social norms using coordination games: why does dictator game sharing vary? - Erin Krupka; Roberto A. Weber (Institute for the Study of Labor (IZA), 2008)
We explore the influence of social norms on behavior. To do so, we introduce a method for identifying norms, based on the property that social norms reflect social consensus regarding the appropriateness of different possible behaviors. We demonstrate that the norms we elicit, along with a simple model combining concern for norm-compliance with utility for money, predict changes in behavior across several variants of the dictator game in which behavior changes substantially following the introduction of minor contextual variations. Our findings indicate that people care not just about monetary payoffs but also care about the social appropriateness of any action they take. Our work also suggests that a social norm is not always a single action that should or should not be taken, but rather a profile of varying degrees of social appropriateness for different available actions.
urn:nbn:de:101:1-20081202191
Keywords: C91; 330; Norms; matching games; dictator games; Soziale Norm; Nichtkooperatives Spiel; Verhaltensökonomik; Test